2008
DOI: 10.22237/jmasm/1225513500
|View full text |Cite
|
Sign up to set email alerts
|

On Some Properties of Quasi-Negative-Binomial Distribution and Its Applications

Abstract: The quasi-negative-binomial distribution was applied to queuing theory for determining the distribution of total number of customers served before the queue vanishes under certain assumptions. Some structural properties (probability generating function, convolution, mode and recurrence relation) for the moments of quasi-negative-binomial distribution are discussed. The distribution's characterization and its relation with other distributions were investigated. A computer program was developed using R to obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Formally, negative binomial is the count of the number of trials in a series of independent and identically distributed binary trials until a specified number of successes (or failures) occurs, and the Poisson is the count of times an event occurs in a period of time. Both distributions assume each event is independent; however, because people change their behaviour based on recent experiences, this may not always be true (Hassan & Bilal, 2008 ). For example, a person’s preference for choosing to exercise might change based on recent experience.…”
Section: Count Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formally, negative binomial is the count of the number of trials in a series of independent and identically distributed binary trials until a specified number of successes (or failures) occurs, and the Poisson is the count of times an event occurs in a period of time. Both distributions assume each event is independent; however, because people change their behaviour based on recent experiences, this may not always be true (Hassan & Bilal, 2008 ). For example, a person’s preference for choosing to exercise might change based on recent experience.…”
Section: Count Distributionsmentioning
confidence: 99%
“…This is a pity, as the distribution has the type of properties we would be interested in. Specifically, where there are not an oversupply of zeros it can often produce a good fit for more highly skewed data as it has a ‘fat tail’ – more extreme high values 3 (Hassan & Bilal, 2008 ; Li, Yang, Famoye, Lee, & Black, 2011 ).…”
Section: Count Distributionsmentioning
confidence: 99%
“…The quasi-negative binomial distribution Janardan (1975); Sen & Jain (1996) and very recently by Li et al (2011) has the probability mass function Hassan & Bilal (2008) of the form:…”
Section: The Quasi-negative Binomial-qnbdmentioning
confidence: 99%
“…That is, we have observations designated in k+ categories. We give example below, which is adapted from Hassan & Bilal (2008) and relates to the number of absenteeism among shift workers in steel industry as reported in Arbous & Sichel (1954). The category 25+ actually stands for counts in categories (25-48) and are combined in that category with a frequency count of 16.…”
Section: The Extended Com-poisson (Ecomp) Distributionmentioning
confidence: 99%
“…He also explored its properties with an application to the fluctuations of sample function of stochastic process. Nandi and Das (1994) also obtained a class of Abel series distributions Hassan and Bilal (2008). showed that the QNBD model belongs to a family of Abel series distributions by taking the Abel series expansion of…”
mentioning
confidence: 99%